Archival strategies and techniques - Hill, Michael R., 1954- (Newbury Park, Calif. ; London : SAGE, 1993)
This practical and concise book provides an introduction for the novice on conducting archival research and covers such topics as contacting and preparing to work in archives, the protocol of using archives, and ways of organising and referencing the useful data from the archive.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology; Social sciences -- Archival resources